Pengaruh Pelatihan Dan Pengembangan Karir Terhadap Kinerja Karyawan Dengan Employee Engagement Sebagai Variabel Intervening - Ahmad Yani Kosali (Tirtayasa Ekonomika, 2023)
This study aims to analyze the effect of training dan career development on employee performance with employee engagement as an intervening variable for Sinergi Sriwijaya Peduli Office employees. The sampling technique used in this research is non-probability sampling, which is a saturated sample of 40 employees who are the staff level and have a minimum two years of work. The data analysis method in this study used path analysis with the help of SPSS 26 software. The result of this study indicate that 1) training has a effect on employee engagement 2) career development has a effect on employee engagement 3) training and career development has a effect on employee engagement simultaneously 4) training has no effect on employee performance 5) career development has no effect on employee performance 6) training, career development, and employee engagement has a effect on employee performance simultaneously. The Sobel test showed the employee engagement has an indirect effect on each training and career development variable on employee performance.